Method for improving conductivity of positive electrode of lithium ferric manganese phosphate battery
By introducing organic matter on the surface of the positive electrode material of the iron manganese lithium battery and forming a conductive polymer, the problem of low conductivity of the positive electrode material is solved, and the cycling performance is improved and the growth of DCR is reduced.
Patent Information
- Application Number
- CN202510062117.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The conductivity of the positive electrode material of the iron manganese lithium phosphate battery is low, resulting in the growth of cycling performance and DC internal resistance (DCR).
The conductivity of the positive electrode material is improved by introducing organic matter on the surface of the positive electrode material and activate the elastic conductive polymer through a small current during the decomposition process.
It effectively reduces the diaphragm resistivity and electrode plate resistance, improves the cycling performance of ferromanganese lithium phosphate batteries, and slows down the growth of DCR.
Smart Images

Figure HDA0005243198170000011 
Figure HDA0005243198170000012
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion battery design and manufacturing technology, and in particular to a method for improving the conductivity of a positive electrode of a lithium iron manganese phosphate battery. Background Art
[0002] With the increase in electric vehicles and the gradual expansion of energy storage, the focus on battery safety is also gradually increasing. Lithium iron phosphate batteries have gradually become the main positive electrode material for electric vehicles or energy storage batteries due to their high safety. With the advancement of technology and the upgrading of materials, the gram capacity of lithium iron phosphate has almost reached its limit, and there is not much room for performance improvement. The crystal structure of lithium iron manganese phosphate is similar to that of lithium iron phosphate. It also has the characteristics of stable chemical properties and excellent safety performance. In addition, the doping of manganese in lithium iron manganese phosphate can increase the charging voltage of the material. Its theoretical energy density is increased by 15% to 20% compared with lithium iron phosphate, which can further expand the cruising range.
[0003] However, due to the addition of manganese, the conductivity of lithium iron manganese phosphate material is poor, only 10 -13 S / cm. The conductivity of lithium iron manganese phosphate materials can be improved by carbon coating on the surface. However, carbon coating on the surface of positive electrode materials requires special equipment and processes, which will increase the manufacturing cost of raw materials. In addition, carbon coating on the surface of lithium iron manganese phosphate materials can only solve the conductivity of a single particle. In the preparation of the pole piece, more conductive agents must still be added to reduce the membrane resistance of the pole piece, improve the electrochemical properties of the pole piece, and improve the cycle performance and DC internal resistance (DCR) growth of lithium iron manganese phosphate batteries. Summary of the invention
[0004] Based on the problems existing in the above-mentioned prior art, the present invention provides a method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery, aiming to reduce the carbon coating amount of the lithium iron manganese phosphate material and the amount of conductive agent in the electrode sheet while reducing the membrane resistivity and the electrode sheet resistance through the method of the present invention, thereby improving the cycle performance and DCR growth problem of the lithium iron manganese phosphate.
[0005] The present invention first provides a method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery, comprising the following steps:
[0006] (1) preparing lithium iron manganese phosphate, PVDF, a composite conductive agent and an organic matter into a slurry by a conventional slurrying process;
[0007] (2) coating the slurry on both sides of aluminum foil or carbon-coated aluminum foil and drying it to obtain a lithium iron manganese phosphate positive electrode coil;
[0008] (3) rolling the electrode coil obtained in step (2) to obtain a lithium iron manganese phosphate positive electrode sheet;
[0009] (4) Assembling the lithium iron manganese phosphate positive electrode sheet and the negative electrode into a full battery, and injecting and soaking after the moisture content is qualified;
[0010] (5) The soaked battery cell is chemically processed and then subjected to subsequent trial production to obtain a finished battery cell.
[0011] Preferably, in the lithium iron manganese phosphate, Mn accounts for 10% to 90% of the total molar content of Mn and Fe; the surface of the lithium iron manganese phosphate primary particles is carbon-coated or non-carbon-coated.
[0012] Preferably, the composite conductive agent is composed of single-walled carbon nanotubes, multi-walled carbon nanotubes and SP conductive agent, and the mass ratio of the three is in the range of 0.1% to 2.0%: 33.3% to 19.6%: 66.6% to 78.4%.
[0013] Preferably, the organic matter comprises at least one of aromatic, benzene, non-benzene and heterocyclic organic matter, wherein the aromatic organic matter is aromatic amine or styrene, the benzene organic matter is aniline, the non-benzene organic matter is 1,8-diaminonaphthalene or 1-aminoanthracene, and the heterocyclic organic matter is pyrrole, thiophene or indole.
[0014] Preferably, when the surface of the lithium iron manganese phosphate primary particles is carbon-coated, the dry matter mass ratio of the carbon-coated lithium iron manganese phosphate, PVDF, composite conductive agent and organic matter is (97-98): (1.0-1.5): (0-1): (0.2-0.8), specifically 97: 1.2: 1: 0.8 or 98: 1.0: 0.5: 0.5. When the surface of the lithium iron manganese phosphate primary particles is not carbon-coated, the dry matter mass ratio of the carbon-free lithium iron manganese phosphate, PVDF, composite conductive agent and organic matter is (95-97): (1.0-1.5): (0.5-2): (0.5-2), specifically 95: 1.4: 1.8: 1.8 or 97: 1.2: 0.3: 1.5;
[0015] Preferably, when preparing the slurry in step (1), PVDF and organic matter are added to NMP in proportion for sizing, the solid content of the slurry is adjusted to 6% to 10%, and then a composite conductive agent is added for high-speed dispersion, and then the lithium iron manganese phosphate material is added to the solvent for slurrying. The solid content of the slurry is 50% to 65%, and the viscosity is 4000 to 7000 mpas.
[0016] Preferably, in step (2), the slurry is coated on the surface of the aluminum foil or carbon-coated aluminum foil with a double-sided surface density of 320 to 430 g / m 2 .
[0017] Preferably, in step (3), the compaction density of the roller pressing is 2.3 to 2.5 g / cm 3 .
[0018] Preferably, in step (4), the formation process includes a low current activation process to promote the electro-oxidation polymerization of organic matter on the surface of the positive electrode to generate a conductive polymer, specifically, 0.01C constant current charging to 1.8V, 0.02C constant current charging to 2.7V. The subsequent formation process is consistent with the formation process of conventional lithium iron manganese phosphate batteries.
[0019] The method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery of the present invention can introduce organic matter that can be adsorbed on the surface of the positive electrode material, and after being formed by a small current, a layer of elastic conductive polymer is formed on the surface of the positive electrode material, which can effectively improve the problem of separation between the positive electrode material and the traditional conductive agent caused by the volume change of the positive electrode material during the lithium insertion and extraction process, effectively improve the conductivity of the positive electrode material during the cycle process, reduce the DCR growth during the cycle process and improve the cycle performance.
[0020] The present invention has the following beneficial effects:
[0021] The present invention aims at the problem of low conductivity of lithium iron manganese phosphate positive electrode materials and provides a solution for improving conductivity at the battery cell end. Due to the incorporation of manganese elements, the conductivity of lithium iron manganese phosphate positive electrode materials is very low. After the conductive organic matter is fully and evenly mixed with the positive electrode material, a layer of elastic conductive polymer is formed on the positive electrode surface through electro-oxidation polymerization during the initial formation period, which effectively improves the positive electrode membrane resistivity. The cycle performance of the lithium iron manganese phosphate battery cell is improved by optimizing the membrane resistivity, and the DCR growth during the cycle process is reduced. The entire production process of the present invention fully matches the mass production battery cell process and has a high application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Comparison of room temperature cycle capacity retention rates of the cells prepared in Examples 1 and 2 and Comparative Examples 2 and 3;
[0023] Figure 2 Comparison of the DCR growth rates of the cells prepared in Examples 1 and 2 and Comparative Examples 2 and 3 during normal temperature cycling. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0025] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0026] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0027] The following percentages, unless otherwise specified, are by mass.
[0028] Example 1
[0029] Using NMP as solvent, carbon-coated lithium iron manganese phosphate (commercially available material, Mn molar ratio is 60%), PVDF, composite conductive agent (composite of single-walled carbon nanotubes, multi-walled carbon nanotubes and SP conductive agent at a mass percentage of 1.0%: 32.4%: 66.6%), and 1,8-diaminonaphthalene are wet-mixed at a mass ratio of 98: 1.0: 0.5: 0.5 to prepare a positive electrode slurry with a solid content of 55.1% and a viscosity of 4583mpas. The slurry is filtered using a 200-mesh capsule filter, and then the slurry is coated on both sides of the aluminum foil. The coating speed is set to 15m / min, the maximum baking temperature of the coating oven is 110°C, and the overall surface density of the coating is 400g / m 2 The coated positive electrode roll was transferred to the roller press. After roller pressing, the positive electrode compaction density was 2.35g / cm 3 The rolled positive electrode is cut by laser slitting to obtain the electrode sheet and then stacked and assembled with the matching graphite negative electrode to prepare a square shell battery with a battery capacity of 86Ah. The moisture content of the battery cell is less than 200ppm after vacuum baking. The battery cell is injected and infiltrated, and then formed. The formation process is 0.01C charging to 1.8V, 0.02C charging to 2.7V, 0.03C charging to 3.0V, 0.08C charging to 3.4V, and 0.2C charging to 3.7V. The formed battery cell is aged, refilled and sealed, and then charged and discharged at 0.33C for 3 weeks to obtain the finished battery cell.
[0030] Example 2
[0031] Using NMP as solvent, carbon-free lithium iron manganese phosphate (commercially available material, Mn molar ratio is 60%), PVDF, composite conductive agent (composite of single-walled carbon nanotubes, multi-walled carbon nanotubes and SP conductive agent at a mass percentage of 1.0%: 32.4%: 66.6%), and 1,8-diaminonaphthalene are wet-mixed at a mass ratio of 97: 1.2: 0.3: 1.5 to prepare a positive electrode slurry with a solid content of 56.2% and a viscosity of 4123mpa·s. The slurry is filtered using a 200-mesh capsule filter, and then the slurry is coated on both sides of the aluminum foil. The coating speed is set to 15m / min, the maximum baking temperature of the coating oven is 110°C, and the overall surface density of the coating is 400g / m 2 The coated positive electrode roll is transferred to the roller press. After roller pressing, the positive electrode compaction density is 2.35g / cm 3The rolled positive electrode is cut by laser slitting to obtain the electrode sheet and then stacked and assembled with the matching graphite negative electrode to prepare a square shell battery with a battery capacity of 86Ah. The moisture content of the battery cell is less than 200ppm after vacuum baking. The battery cell is injected and infiltrated, and then formed. The formation process is 0.01C charging to 1.8V, 0.02C charging to 2.7V, 0.03C charging to 3.0V, 0.08C charging to 3.4V, and 0.2C charging to 3.7V. The formed battery cell is aged, refilled and sealed, and then charged and discharged at 0.33C for 3 weeks to obtain the finished battery cell.
[0032] Comparative Example 1
[0033] The difference between Comparative Example 1 and Example 1 is that no organic matter is added. Specifically, carbon-coated lithium manganese iron phosphate, PVDF, and a composite conductive agent are wet-mixed in a mass ratio of 98:1.0:1.0, and the operations from slurry mixing to volume separation are the same as those in Example 1.
[0034] Comparative Example 2
[0035] The difference between Comparative Example 2 and Example 1 is that the formation process is different, specifically: the formula and operation from slurry mixing to liquid injection are the same as those in Example 1, the formation process adopts 0.03C charging to 3.0V, 0.08C charging to 3.4V, and 0.2C charging to 3.7V, and the formed battery cell is aged, refilled and sealed, and then charged and discharged at 0.33C for 3 weeks to obtain a finished battery cell.
[0036] Comparative Example 3
[0037] The difference between Comparative Example 3 and Example 2 is that no organic matter is added. Specifically, lithium manganese iron phosphate without carbon coating, PVDF, and composite conductive agent are wet-mixed in a mass ratio of 97:1.2:1.8, and the operations from slurry mixing to volume separation are the same as those in Example 2.
[0038] Comparative Example 4
[0039] The difference between Comparative Example 4 and Example 2 is that the formation process is different, specifically: the formula and operation from slurry mixing to liquid injection are the same as those in Example 2, the formation process adopts 0.03C charging to 3.0V, 0.08C charging to 3.4V, and 0.2C charging to 3.7V, and the formed battery cell is aged, refilled and sealed, and then charged and discharged at 0.33C for 3 weeks to obtain a finished battery cell.
[0040] The comparison of the film resistivity and the internal resistance of the whole battery of the electrode sheets prepared in each embodiment and comparative example is shown in Table 1.
[0041] Table 1
[0042] Grouping Film resistivity Internal resistance of the whole battery Example 1 0.335Ω·cm 0.403mΩ Example 2 0.392Ω·cm 0.421mΩ Comparative Example 1 0.409Ω·cm 0.455mΩ Comparative Example 2 0.367Ω·cm 0.412mΩ Comparative Example 3 0.432Ω·cm 0.464mΩ Comparative Example 4 0.401Ω·cm 0.442mΩ
[0043] From the comparison between the diaphragm resistance and the internal resistance of the whole battery, it can be seen that adding organic matter during the slurry mixing process to form a layer of elastic conductive polymer on the surface through small current oxidation in the formation stage can effectively improve the diaphragm resistivity and the internal resistance of the whole battery of the lithium iron manganese phosphate positive electrode.
[0044] Figure 1 and Figure 2 By comparing the room temperature cycle capacity retention rate and DCR growth rate of the battery cells of the embodiment and two comparative examples (50% SOC, 1.5C discharge for 10s), it can be seen that the introduction of the elastic conductive polymer effectively improves the cycle of the battery cell and reduces the growth of DCR.
[0045] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery, characterized in that: (1) preparing lithium iron manganese phosphate, PVDF, a composite conductive agent and an organic matter into a slurry by a slurrying process; (2) coating the slurry on both sides of aluminum foil or carbon-coated aluminum foil and drying it to obtain a lithium iron manganese phosphate positive electrode coil; (3) rolling the electrode coil obtained in step (2) to obtain a lithium iron manganese phosphate positive electrode sheet; (4) Assembling the lithium iron manganese phosphate positive electrode sheet and the negative electrode into a full battery, and injecting and soaking after the moisture content is qualified; (5) The soaked battery cell is chemically processed and then subjected to subsequent trial production to obtain a finished battery cell.
2. The method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery according to claim 1, characterized in that: In the lithium iron manganese phosphate, Mn accounts for 10% to 90% of the total molar content of Mn and Fe; the surface of the primary particles of the lithium iron manganese phosphate is carbon-coated or not carbon-coated.
3. The method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery according to claim 1, characterized in that: The composite conductive agent is composited from single-walled carbon nanotubes, multi-walled carbon nanotubes and SP conductive agent.
4. The method for improving the conductivity of the positive electrode of a lithium iron manganese phosphate battery according to claim 2, characterized in that: When the surface of the lithium iron manganese phosphate primary particles is carbon-coated, the dry matter mass ratio of the carbon-coated lithium iron manganese phosphate, PVDF, composite conductive agent and organic matter is 97-98:1.0-1.5:0-1:0.2-0.8; When the surface of the lithium iron manganese phosphate primary particles used is not carbon-coated, the dry matter mass ratio of the carbon-free lithium iron manganese phosphate, PVDF, composite conductive agent and organic matter is 95-97:1.0-1.5:0.5-2:0.5-2.
5. The method for improving the conductivity of lithium iron manganese phosphate positive electrode according to claim 1, characterized in that: In step (1), the solid content of the slurry is 50% to 65%, and the viscosity is 4000 to 7000 mpas.
6. The method for improving the conductivity of lithium iron manganese phosphate positive electrode according to claim 1, characterized in that: In step (2), the slurry is coated on both sides of the aluminum foil or carbon-coated aluminum foil with a double-sided surface density of 320 to 430 g / m 2 In step (3), the compaction density of the roller is 2.3 to 2.5 g / cm 3 .
7. The method for improving the conductivity of lithium iron manganese phosphate positive electrode according to claim 1, characterized in that: In step (5), the formation process includes first charging at a constant current of 0.01C to 1.8V, then charging at a constant current of 0.02C to 2.7V, and then performing the remaining formation according to a conventional formation process.
8. The method for improving the conductivity of lithium iron manganese phosphate positive electrode according to claim 1, characterized in that: The organic matter comprises at least one of aromatic, benzene, non-benzene and heterocyclic compound organic matter.
9. The method for improving the conductivity of lithium iron manganese phosphate positive electrode according to claim 8, characterized in that: Aromatic organic compounds include aromatic amines or styrene, benzene organic compounds include aniline, non-benzene organic compounds include 1,8-diaminonaphthalene or 1-aminoanthracene, and heterocyclic organic compounds include pyrroles, thiophenes or indoles.
Citation Information
Patent Citations
Lithium ion battery positive pole and preparation method thereof
CN103107309A
Poly (1, 8-diaminonaphthalene) nanosheet material, preparation method thereof, electrode material and supercapacitor
CN112661960A
Method for forming lithium ion battery and lithium ion battery
CN114497776A
Preparation method of conductive polymer positive electrode material with high doping availability
CN115275192A
Wide-temperature type lithium manganese iron phosphate battery and preparation method thereof
CN115513441A